THE SHARIAH-BASED HEDGING INSTRUMENTS USED FOR MANAGING THE FOREIGN EXCHANGE RATE-RELATED RISKS - Dr. Hiyam Mohammad Al-Zedaneen, Dr. Omar Yacoub Ibrahim Abdelrahim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The foreign exchange rate-related risks are considered the most significant risks in international markets. That is because there are many currencies which exchange rates are connected with each other. One of the reasons behind such risks is the time difference between locations worldwide. That is because the foreign currencies are exchanged 24 hours/day in foreign exchange markets. The fluctuation in the foreign exchange rates is a risk to capital. Facing this risk requires employing hedging instruments (including conventional and Shariah-based hedging instruments).